2019
DOI: 10.1002/jsde.12323
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Polypeptide/Phospholipid Monolayers on Water and the Plasma‐Activated Polyetheretherketone Support

Abstract: Polyetheretherketone (PEEK) is a highly biocompatible polymer widely used in medicine as an implant production material. In this article, the PEEK surface was characterized in terms of its wettabillity properties after the physicochemical modifications by treatment with the low‐temperature air plasma and covering with the Langmuir–Blodgett (LB) monolayers of polypeptide (cyclosporine A, CsA) and/or phospholipid (1,2‐dipalmitoyl‐sn‐glycero‐3‐phosphocholine, DPPC). The LB deposition was preceded by the analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Each of the compounds studied here (DOPC, CsA, and LG) forms true Langmuir monolayers at the air−water interface, as shown in Figure 1, with the isotherms being consistent with the data published previously. 3,34 Here, the "true" term means that the layer-forming molecules are practically insoluble in the water subphase and these molecules are capable of forming a two-dimensional film at the interface upon the compression process. The π−A curves exhibit a small slope, which is characteristic of high monolayer compressibility.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Each of the compounds studied here (DOPC, CsA, and LG) forms true Langmuir monolayers at the air−water interface, as shown in Figure 1, with the isotherms being consistent with the data published previously. 3,34 Here, the "true" term means that the layer-forming molecules are practically insoluble in the water subphase and these molecules are capable of forming a two-dimensional film at the interface upon the compression process. The π−A curves exhibit a small slope, which is characteristic of high monolayer compressibility.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Using such a less complicated system is very useful to gain information on the binding of proteins to membranes highly dependent on the mutual interactions. Several studies have shown that the poorly water-soluble CsA penetrates lipid membranes showing affinity to the gel/fluid boundaries and disrupts the order of acyl chains, especially around the polar heads. , Its interactions with phospholipids (DPPC, POPC, DPPE, DPPS, DPPG) ,− with a dominant repulsive character generate no miscibility or only partial miscibility. Therefore, the incorporation of the LG antioxidant, which interacts with both DOPC and CsA, can increase the miscibility of these two components and improve the mixture stability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dual-modified PEEK was more favorable for pre-osteoblast adhesion, spreading, and proliferation. Plasma and laser techniques can also be used to immobilize biomolecules on the PEEK surface [ 74 , 82 , 83 , 84 , 85 , 86 ]. Terpiłowski et al [ 74 ] pre-treated PEEK with nitrogen plasma to further immobilize chitosan on its surface.…”
Section: Peek Bioactivitymentioning
confidence: 99%